Building Blocks for Molecular Polygons Based on Platinum Vertices and Polyynediyl Edges - Collins, Brenna K.; Weisbach, Nancy; Hampel, Frank; Bhuvanesh, Nattamai; Gladysz, John A. (Organometallics, 2023)
Reactions of Cl2P(CH2)3PCl2 and p-MgBrC6H4X (X = a/OMe, b/OtBu, c/tBu, d/SiMe3) give the diphosphines (pXC6H4)2P(CH2)3P(p-C6H4X)2 (1a-d; 47-66%). Additions of 1a,d to (COD)PtCl2 yield (CH2(CH2P(p-C6H4X)2)2)PtCl2 (2a,d; 62-88%), which upon reaction with butadiyne (2 equiv; HNEt2/ cat. CuI) give (CH2(CH2P(p-C6H4X)2)2)Pt((C-C)2H)2 (3a,d; 34-76%). Alternatively, 3a-d can be accessed from trans-(ptol3P)2Pt((C-C)2H)2 and 1a-d (30-87%). Reactions of (ptol3P)2PtCl2 and H(C-C)2SiR3 (2 equiv, HNEt2/cat. CuI; R = Me/Et/iPr) give trans-(p-tol3P)2Pt((C-C)2SiR3)2 (77-95%), and subsequent additions of 1a,b,d yield the corresponding adducts (CH2(CH2P(p-C6H4X)2)2)Pt((C-C)2SiR3)2 (R/X = Me/OMe, 5a; iPr/OMe, 6a; iPr/OtBu, 6b; iPr/SiMe3, 6d; 52-95%) and (for 5a) a luminescent diplatinum byproduct with trans Pt((C-C)2SiMe3)2 units. 5a and 6b hydrolyze in the presence of F- to 3a,b (92-93%). Reaction of 2a and 3a (HNEt2/cat. CuI) affords the Pt4C16 polygon ([(CH2(CH2P(p-C6H4OMe)2)2)Pt(C-C)2]4 as an H2NEt2+ Cl- adduct (66%). The 13C1H NMR spectra of 3a-d, 5a, and 6a,b,d feature complex AMXX ' (CPtPP ') spin systems, and simulations allow J values to be extracted. The crystal structures of 2a, 3a,b,d, 5a, and 6a are determined and analyzed.
CRIS-Team WoS Importer:2023-03-17